Ga2Se3 treatment of Cu-rich CIGS thin films to fabricate Cu-poor CIGS thin films with large grains and U-shaped Ga distribution. (June 2018) - Peng, Xiao; Zhao, Ming; Zhuang, Daming; Sun, Rujun; Zhang, Leng; Wei, Yaowei; Lv, Xunyan; Wu, Yixuan; Ren, Guoan
Abstract: Cu-rich CIGS thin films were prepared from quaternary CIGS and Cu target, and then converted into Cu-poor CIGS by depositing the Ga2 Se3 layer on the Cu-rich CIGS with the subsequent annealing. In this paper, we name the process of converting Cu-rich CIGS into Cu-poor CIGS as Ga2 Se3 treatment. The Ga2 Se3 treatment brings out two benefits for the CIGS absorbers. It can remove the excess Cu x Se phase in the Cu-rich CIGS and don't reduce the grain size of CIGS. That is to say, the Cu-poor CIGS has almost the same size of grain of the Cu-rich CIGS thin films. What's more, the Ga2 Se3 treatment can also improve the content of gallium on the surface of CIGS, resulting the U-shaped gallium distribution along the depth direction. The thickness of Ga2 Se3 layer has been optimized which can result in the highest conversion efficiency of 10.6% in Cu-rich CIGS based solar cells. Highlights: CIGS thin films with grain size above 1 μm were fabricated from the Ga2 Se3 -treated Cu-rich CIGS thin films. The Ga2 Se3 -treated Cu-rich CIGS thin films have U-shaped gallium distribution along the depth direction. Cells based on the Ga2 Se3 -treated Cu-rich CIGS thin films have achieved the highest efficiency of 10.6%.